Confocal laser imaging in neurosurgery: A comprehensive review of sodium fluorescein-based CONVIVO preclinical and clinical applications - Restelli, Francesco; Mathis, Andrea Maria; Höhne, Julius; Mazzapicchi, Elio; Acerbi, Francesco; Pollo, Bianca; Quint, Karl (Frontiers in Oncology, 2022)
Given the established direct correlation that exists among extent of resection and postoperative survival in brain tumors, obtaining complete resections is of primary importance. Apart from the various technological advancements that have been introduced in current clinical practice, histopathological study still remains the gold-standard for definitive diagnosis. Frozen section analysis still represents the most rapid and used intraoperative histopathological method that allows for an intraoperative differential diagnosis. Nevertheless, such technique owes some intrinsic limitations that limit its overall potential in obtaining real-time diagnosis during surgery. In this context, confocal laser technology has been suggested as a promising method to have near real-time intraoperative histological images in neurosurgery, thanks to the results of various studies performed in other non-neurosurgical fields. Still far to be routinely implemented in current neurosurgical practice, pertinent literature is growing quickly, and various reports have recently demonstrated the utility of this technology in both preclinical and clinical settings in identifying brain tumors, microvasculature, and tumor margins, when coupled to the intravenous administration of sodium fluorescein. Specifically in neurosurgery, among different available devices, the ZEISS CONVIVO system probably boasts the most recent and largest number of experimental studies assessing its usefulness, which has been confirmed for identifying brain tumors, offering a diagnosis and distinguishing between healthy and pathologic tissue, and studying brain vessels. The main objective of this systematic review is to present a state-of-the-art summary on sodium fluorescein-based preclinical and clinical applications of the ZEISS CONVIVO in neurosurgery.